Basal ganglia stroke is associated with altered functional connectivity of the left inferior temporal gyrus. Issue 4 (17th February 2022) - Li, Zhongming; Hu, Jianping; Wang, Zhimin; You, Ruixiong; Cao, Dairong
Abstract: Background and Purpose: Acute cerebral infarction in the basal ganglia is associated with an increased risk of cognitive impairment, suggesting that cognitive networks might be involved in neural plasticity after ischemic stroke. This study was conducted to explore the abnormalities in functional and causal connectivity of the brain network in patients with acute ischemic stroke (AIS) in the basal ganglia. Methods: Resting‐state functional magnetic resonance imaging was performed in 27 patients with AIS in the basal ganglia and 27 healthy controls (HCs). Brain regions with statistically different degree centrality (DC) values between groups were selected as seed points for granger causality analysis (GCA) analysis. The effective connectivity values of GCA were extracted, and the correlation between them and the Montreal Cognitive Assessment (MoCA) score was analyzed. Results: Compared with HCs group, AIS patients displayed increased DC value in the left inferior temporal gyrus (ITG) and hippocampus head, reduced effective connectivity from the left ITG to the left precentral and postcentral gyri, increased effective connectivity from the left precentral and postcentral gyri to the left ITG, and reduced effective connectivity from the left anterior cingulate gyrus to the left ITG. The MoCA score of the AIS group was lower than that of the HCs group ( t = –7.33, p < .05). Conclusion: Alterations of functional and causal connectivity among multiple brain regions suggest that patients with AIS in the basal ganglia have impairment of multifunctional networks in the whole brain.